A MULTI-CRITERIA DECISION-MAKING APPROACH FOR GREENOVATIVE SUPPLIER SELECTION - Çaloğlu Büyükselçuk, Elif; Tozan, Hakan; Vayvay, Özalp (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
In today’s rapidly changing business environment, green and innovative (greenovative) activities have become indispensable elements of sustainable supply network management. Realization of this fact obliges firms to consider greenovative as well as traditional criteria in determining their supplier. This study provides a new greenovative systematic approach to supplier selection for small and medium-sized enterprises. Fuzzy multi-criteria decision-making (FMCDM)-based techniques were used to determine the most appropriate supplier with the proposed model. To show the usability of the model, an application was carried out on an automotive supply company. Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (FAHP) approaches were used to calculate the weights of the supplier selection criteria. After determining criteria weights, different multi-criteria decision-making (MCDM) techniques that are often encountered in the literature were used to identify the best supplier.